Pengaruh Corporate Social Responsibility, Leverage, dan Woman On Board Terhadap Firm Value - Alien Puspitasari; Ceacilia Srimindarti (Owner : Riset dan Jurnal Akuntansi, 2022)
Firm value (company value) is the value owned by a company company, whether it gets local or foreign capital obtained based on several important things that can build the company from the beginning until now. This preparation has the aim of testing and analyzing the effect of corporate social responsibility, leverage, and woman on board on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the last three periods, 2018-2020, with a population of 536 company. The sampling method used in this study is a purposive sampling technique with several selected criteria so as to obtain a sample of 258 companies. This study uses secondary data in the form of numbers that are processed into a statistical measurement scale. Data collection techniques using documentation techniques. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that corporate social responsibility (CSR) and woman on board (WoB) have a negative effect on firm value. Meanwhile, leverage (DER) has a significant effect in a positive direction on firm value. Keywords:corporate social responsibility; leverage; woman on board; firm value